"Simultaneous optimization model for thinning and harvesting Alnus acuminata and Pinus patula plantations in Southern Ecuador". Issue 2 (3rd April 2021) - Valle-Carrión, Liz; Hildebrandt, Patrick; Castro, Luz Maria; Ochoa-Moreno, Wilman-Santiago; Knoke, Thomas
ABSTRACT: Sustainable forest management requires tools to guide optimal silvicultural treatments. Timing and intensity of thinnings and timing of final harvest are key decisions. An Optimized Reforestation Management (herein, an ORM) model was developed to reach the optimal combination of thinning times, thinning intensities and rotation periods for Ecuadorian forest plantations of Alnus acuminata, Kunth and Pinus patula Schltdl. & Cham. The ORM model uses non-linear programing to simultaneously optimize the number of trees to harvest in a certain period in order to maximize the plantations' annualized net present values (annuities). Results obtained for optimal silvicultural interventions were compared to current management practices in Ecuador, one with no interventions, and a second with a treatment schedule promoted by the Ecuadorian Ministry of Agriculture. ORM model delivered better financial performance for both species, compared to both alternative scenarios, in terms of annuities and payback periods. Thinnings scheduled by ORM tend to be later than recommended by existing schedules. For Alnus, only one thinning was optimal, independent of the discount rate, while for Pinus two thinnings were optimal for higher levels of the discount rate considered. It is recommended for private and public actors to consider these findings for future management of reforestation areas.